2013
DOI: 10.1111/eci.12124
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection associated with high HbA1c and type 2 diabetes

Abstract: Long-term H. pylori infection is significantly associated with high levels of HbA1c and decreased insulin secretion in this Chinese population. Proper screening for H. pylori infection combined with regular monitoring of blood glucose and HbA1c levels might be effective for the early detection of glucose dysregulation and prevention of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 38 publications
3
65
0
2
Order By: Relevance
“…Hsiech et al found that the HbA1c levels of Hp positive patients were significantly higher than those of Hp negative in their study including 2060 patients in China. Also, in that study, type 2 diabetes frequency was significantly higher in the Hp-positive group [8].…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Hsiech et al found that the HbA1c levels of Hp positive patients were significantly higher than those of Hp negative in their study including 2060 patients in China. Also, in that study, type 2 diabetes frequency was significantly higher in the Hp-positive group [8].…”
Section: Resultsmentioning
confidence: 51%
“…Considering from another respect, DM was observed to be more prevalent in Hp-positive patients in the study by Han et al which included 30810 patients and was completed in 2015 in China (21.3% and 20.2%, p=0.026) [6]. Also, numerous studies including large patient populations revealed that the HbA1c levels of Hp-positive diabetic patients were higher than that of Hp-negative diabetic patients, suggesting that bacterial infection may have had a negative effect on blood glucose regulation in infected patients [7,8]. We investigated whether there is any significant difference in metabolic control namely HbA1c levels among the patients having diabetes with dyspeptic complaints who underwent endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…pylori infection is reported to be associated with insulin resistance, diabetes mellitus and metabolic syndrome [74][75][76] . Compared to non-diabetics with HPI, the levels of oxidative DNA damage (8-OHdG) in type 2 diabetes mellitus could be much higher (p = 0.001).…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…There were significant differences of fasting blood glucose, high-density lipoprotein cholesterol between HPI patients and healthy controls [75] . Hsieh et al reported that long-term HPI was significantly associated with increased levels of HbA1c and decreased insulin secretion in Chinese population [76] .…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Proper screening for Hp infection combined with regular monitoring of blood glucose and HbA1c levels might be effective for the early detection of glucose dysregulation and prevention of T2DM [25]. An analysis performed on 5889 subjects showed that metabolic syndrome was more strongly associated with histologic positivity for Hp than serologic positivity, after adjusting for age, sex, smoking status, alcohol consumption, and economic status.…”
Section: Metabolic Changes In Hp With T2dmmentioning
confidence: 99%